2015
DOI: 10.1515/intag-2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Critical soil bulk density for soybean growth in Oxisols

Abstract: The aim of this study was to evaluate the critical soil bulk density from the soil penetration resistance measurements for soybean root growth in Brazilian Amazon Oxisols. The experiment was carried out in a greenhouse using disturbed soil samples collected from the northwest of Para characterized by different texture. The treatments consisted of a range of soil bulk densities for each soil textural class. Three pots were used for soybean growth of and two for the soil penetration resistance curve. From the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…directly affected the addition of soil water content in soil and affect the soil bulk density becomes lower with a correlation coefficient of 0.99 (Figure 2). So, the correlation between SWC and SBD has a negative correlation, as stated by Hillel ( 2004) and (Korenkova and Urik, 2017).Previous researches by Kormanek et al (2015) and Sato et al (2015) confirmed that decreasing tendency for root system length with an increase in the level of SBD by the slope of trends line of regression equation in forest tree and soybean plant with correlation coefficient in both cases appear to be significance level.…”
Section: The Reciprocal Relationshipmentioning
confidence: 70%
See 1 more Smart Citation
“…directly affected the addition of soil water content in soil and affect the soil bulk density becomes lower with a correlation coefficient of 0.99 (Figure 2). So, the correlation between SWC and SBD has a negative correlation, as stated by Hillel ( 2004) and (Korenkova and Urik, 2017).Previous researches by Kormanek et al (2015) and Sato et al (2015) confirmed that decreasing tendency for root system length with an increase in the level of SBD by the slope of trends line of regression equation in forest tree and soybean plant with correlation coefficient in both cases appear to be significance level.…”
Section: The Reciprocal Relationshipmentioning
confidence: 70%
“…Sato et al (2015) use the concept of soil penetration resistance (PR), found that the relationship between soil water content and soil bulk is non-linear in soybean plants. The model…”
mentioning
confidence: 99%
“…Spoil material such as glacial till is highly prone to compaction [59] and even deep soil loosening during cultivation is very quickly invisible [46]. A high BD (close to 2.0 Mg m −3 ) found in Cd horizons was limiting for plant root development [60][61][62], at the same time indicating the achievement of maximum values for till [63,64]. In the case of particle density (PD), the 43-year development of Technosols under agricultural reclamation resulted in marked profile variation that was not observed in 1978.…”
Section: Changes In Technosols' Propertiesmentioning
confidence: 99%